Differential Expression of Low Mr GTP-binding Proteins in Human Megakaryoblastic Leukemia Cell Line, MEG-01, and their Possible Involvement in the Differentiation Process - Nagata, Koh-ichi; Okano, Yukio; Nozawa, Yoshinori (Thrombosis and Haemostasis, 1997)
The expression of various low Mr GTP-binding proteins at various states of differentiation of a human megakaryoblastic leukemia cell line, MEG-01, was analyzed using thermocycle amplification of mRNA and immunoblotting. MEG-01 cells were found to express mRNAs of rap1A, rap1B, rap2B, ralA, rhoA, rac1, rac2, CDC42Hs, rab1, rab3B, rab6, ram and ran, but not rab4, and the proteins of Rap 1, Rap2, RhoA, Rac1, Rac2, Rab3B, Rab4, Rab6 and Rab8 were expressed. Differentiation of MEG-01 cells induced by 100 nM 12-O-tetradecanoylphorbol-13-acetate revealed the considerable increases in mRNA expression of rap1B, rab3B, rabA, ram and ran whereas the levels of rap2B, rhoA and rac1 decreased. During the differentiation process, significant changes in protein levels of Rap1, RhoA, Rac1, Rac2, Rab3B, Rab4 and Rab6 were observed among three subcellular (cytosol, Triton X-100-soluble membrane and -insoluble cytoskeleton) fractions. The present investigation may be useful for the study of the megakaryocyte differentiation.